Idiomatic Expressions in J.K. Rowling’s Harry Potter and The Prisoner of Azkaban - Amalia, Mutiara; Hilman, Evert H.; Putri , Evi Jovita (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
The paper argues that the quality of idiom translations depends on the appropriate strategy used while translating them because idiomatic expressions cannot be translated from their words. This study was carried out to describe the meaning of the idiomatic expression and the application of Chesterman's strategies in translating idioms and identify the speech acts of the utterances conveyed by the speaker in the data. This research used a descriptive qualitative method. The data were gathered from J.K. Rowling’s Harry Potter and the Prisoner of Azkaban. The study also used their Indonesian version to find out the translation of the idiomatic expressions. One hundred five quotes were taken from the novels. As a result, Unit Shift appears more frequently in the novel as a syntactic strategy followed by Scheme Change. Furthermore, in terms of semantic approach, distribution Change is the most common strategy that emerges from the novels, followed by Trope Change. The Assertive Act is the most dominant act delivered by the speaker behind the utterances in speech acts.